Polarized photoelectrons from converging vector waves - B Hafizi; D Younis; D F Gordon (New Journal of Physics, 2022)
This paper investigates the spin characteristics of photoelectrons when hydrogen-like ions are centro-symmetrically irradiated with converging vector waves—a non-paraxial form of structured light. For a photon with given total angular momentum and third component thereof, photoelectrons with both helicities are obtained—in contrast to the fixed helicities produced by left- or right-circularly polarized light. The angular distribution of photoelectrons is broadly tunable through the radiation mode numbers, and opposite helicities can be extracted in synchronism.